Optimization of wide band mesa-type enhanced terahertz photoconductive antenna at 1550 nm - 徐建星 李金伦 魏思航 马奔 张翼 张宇 倪海桥 牛智川 (Chinese physics B, 2017)
A mesa-type enhanced InGaAs/InAIAs multilayer heterostructure （MLHS） terahertz photoconductive antenna （PCA） at 1550 nm is demonstrated on an InP substrate. The InGaAs/InAIAs superlattice multilayer heterostructures are grown and studied with different temperatures and thickness ratios of InGaAs/InAIAs. The PCAs with different gap sizes and pad sizes are fabricated and characterized. The PCAs are evaluated as THz emitters in a THz time domain spectrometer and we measure the optimized THz bandwidth in excess of 2 THz.